InAs/GaAs quantum dots grown by metal organic chemical vapor deposition at different temperatures - Muhammad, Rosnita (Canadian Center of Science and Eduaction, 2008)
InAs/GaAs quantum dots (QDs) were grown by low pressure Metal Organic Chemical Vapor Deposition in Stranski-Krastanov growth mode. The influence of growth temperature on the QD density was investigated. Atomic Force Microscopy (AFM) was used to study the growth behaviour of the QD structure. It was identified that the growth temperature plays major role in determining the growth and distribution of InAs QDs due to the temperature-dependent dislocation propagation from the GaAs substrate. A high InAs on GaAs QD density 6.4 x 1010 cm-2 was obtained and this proposes a potential superiority of nanodevice operation.